Diversity of Butterfly (Suborder: Rhopalocera) in the Kapopo Grand Forest Park Area, Central Sulawesi - Murni Ammalia; Abd Hakim Laenggeng; Manap Trianto; Masrianih Masrianih; Amalia Buntu; Fatmah Dhafir (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Butterflies are important components of biodiversity, serving as pollinators and environmental bioindicators. This study aimed to assess butterfly diversity (Suborder Rhopalocera) in the Kapopo Grand Forest Park, Central Sulawesi, Indonesia. A quantitative descriptive approach was employed using purposive sampling across three observation stations representing high-vegetation, low-vegetation, and riverine habitats. Data were collected through field surveys conducted during morning and afternoon observation periods, and species were identified based on morphological characteristics. Species diversity was analyzed using the Shannon–Wiener diversity index. A total of 26 butterfly species belonging to three families Nymphalidae, Pieridae, and Papilionidae were recorded, comprising 323 individuals. Nymphalidae was the most species-rich family with 13 species, followed by Pieridae (7 species) and Papilionidae (6 species). The Shannon–Wiener diversity index (H') was 1.5, indicating a moderate level of species diversity (1 <= H' <= 3). This result suggests that habitat conditions within the Kapopo Grand Forest Park remain relatively stable and suitable for sustaining butterfly populations. Variations in habitat characteristics among observation stations, particularly differences in vegetation structure and levels of human disturbance, influenced the distribution and abundance of butterfly species throughout the study area.